German and Thai idioms and Their Semantic Similarities: A Contribution to Cultural Comparison - แสงอร่ามเรือง, วรรณา (Journal of Letters, 2018)
This work was the second of two research projects supported by the Faculty of Arts Research Fund of Chulalongkorn University. Its goal was to discover semantic similarities between German and Thai idioms after the first research project “สำนวนเยอรมันน่ารู้” (Deutsche Redewendungen) had been published. These two projects aimed to assist Thai learners of German as well as translators of German to Thai and vice versa. In this study, German idioms are arranged alphabetically, presented with semantic explanations, examples and their equivalents in Thai, and linked to other German idiomatic expressions with the same or similar meanings. The research aims to answer the following four questions: What cultural aspects do German and Thai idioms have in common? What special features are unique to German idioms? Which main concept is expressed by most of the German idioms? How similar are the idioms of both languages overall?